LITERARY ETHICS IN THE PERSPECTIVE OF ḤADĪTH AND ITS IMPLICATIONS FOR GEN Z IN FACING THE DIGITAL ERA - Siregar, Muhammad Nuh; Rahman, Rahman; Zailani, Zailani; Darussamin, Zikri; Abduh, M. Arrafie; M, Afrizal; Darusman, Darusman (TAJDID: Jurnal Ilmu Ushuluddin, 2025)
In the era of digital disruption, digital literacy is not just about technical skills, but also about ethics and media responsibility. The Gen Z generation, which has grown up with technology, needs a strong foundation of values. This study aims to critically analyse the role of Ḥadīth as a source of values and ethics in shaping Gen Z's digital literacy awareness, so that the use of technology is not only smart, but also moral and responsible. The background of this study is the increasing use of social media and digital platforms that are often misused, such as the spread of hoax news, hatred, and other unethical behaviour. Ḥadīth as one of the authentic sources of Islamic teachings can be used as a guide in shaping critical, ethical, and responsible attitudes in the digital space. This research uses a qualitative method with a literature review approach and content analysis. Data were collected from various Ḥadīth texts related to communication manners, social responsibility, and ethics in conveying information. The results showed that Ḥadīth has a significant role in building digital literacy in the Gen Z generation. Values such as honesty, responsibility in conveying information, and the obligation to verify the truth of information (tabayyun) are very relevant in overcoming the challenges of the digital era. By taking Ḥadīth as a guideline, the Gen Z can be wiser in using digital technology, so that they are able to utilise digital media productively and positively.